Analysis of Nutrition, Quality and Health of Local Pork by Sex - Swacita, Ida Bagus Ngurah; Apsari, Ida; Mufa, Romy Muhammad Dary (Journal of Veterinary and Animal Sciences; Vol 4 No 2 (2021), 2021)
The purpose of this study was to determine the nutrition, quality and health of local Balinese pork based on gender. This study used a qualitative exploratory survey method, which took 10 samples of local pork slaughtered at the Pig Slaughterhouse (TPB), consisting of five female local pork samples and five male samples at three different locations. Assessment of pork nutrition and quality can be done using the Association of Official Analytical Chemist (AOAC) method, while pork health assessment can be done by inspection, palpation, and inches. The results showed that the average nutritional value of male pork was as follows: water content 74.5%, ash 1.2%, crude protein 19.7%, crude fat 4.6%, while the average female pork was water content 74.9 %, ash 1.2%, crude protein 18.8%, crude fat 5.1%. The quality of local pork, both male and female, is reddish brown in color, smells of fresh blood with a soft consistency and smooth texture, the average pH value of male and female pigs is 5.37, and the average water holding capacity of male and female pork is 89.19%. 88.73. The health of the carcass and internal organs of male and female local pigs were normal (healthy), no abnormalities were found, except for a white spot in the liver of the male pig. It can be concluded that the nutrition, quality and health of local pork are in accordance with meat quality standards and are fit for consumption.